Coronary Artery Wall Thickness of the Left Anterior Descending Artery Using High Resolution Transthoracic Echocardiography – Normal Range of Values. Issue 7 (25th January 2013) - Perry, Rebecca; Joseph, Majo X.; Chew, Derek P.; Aylward, Philip E.; De Pasquale, Carmine G.
<x xml:space="preserve">Abstract</x> Recently it has been demonstrated that high resolution transthoracic echocardiography (HRTTE) is able to detect differences in the wall thickness of the left anterior descending coronary artery (LAD) between patients with coronary artery disease (CAD) and normal volunteers. We sought to validate this technique, develop a normal range of values and demonstrate the test–retest variability of each measurement. Two hundred forty‐two volunteer participants had a HRTTE study to measure their LAD wall thickness, luminal, and external diameters. Thirty of these subjects had these measurements taken on 3 separate occasions by 2 different echosonographers. All subjects were free of clinical CAD, hypertension, hyperlipidemia, and diabetes mellitus. The average anterior wall thickness was 1.1 ± 0.2 mm; posterior wall thickness was 1.1 ± 0.2 mm, luminal diameter 2.2 ± 0.6 mm, and external elastic membrane (EEM) diameter 4.5 ± 0.9 mm. The bias of the measurements within the same operator for LAD wall thickness, luminal diameter, and EEM was 0.042, −0.06, and −0.077 mm, respectively. The bias of the measurements between 2 different operators for LAD wall thickness, luminal diameter, and EEM was 0.082, −0.077, and −0.027 mm, respectively. In conclusion, HRTTE measurement of the LAD vessel is reproducible within and between operators in normal volunteers. This technique therefore warrants further study as a potential screening modality for subclinical coronary atherosclerosis.